Study of Load Curves Concerning the Influence of Socioeconomic and Cultural Issues - Gastaldello, Danilo S.; Souza, Andre N. de [UNESP]; Amaral, Haroldo L. M. do [UNESP]; Faria, Pedro; Vale, Zita; IEEE (Ieee, 2014)
The increase of electricity demand in Brazil, the lack of the next major hydroelectric reservoirs implementation, and the growth of environmental concerns lead utilities to seek an improved system planning to meet these energy needs. The great diversity of economic, social, climatic, and cultural conditions in the country have been causing a more difficult planning of the power system. The work presented in this paper concerns the development of an algorithm that aims studying the influence of the issues mentioned in load curves. Focus is given to residential consumers. The consumption device with highest influence in the load curve is also identified. The methodology developed gains increasing importance in the system planning and operation, namely in the smart grids context.
Keywords: Consumption pattern; load curve; planning; residential consumer